Pengaruh Sumberdaya dan Strategi terhadap Kinerja Usaha Rumah Makan di Kota Malang - Andarwati (Universitas Brawijaya, Indonesia, 2014)
The problems of this research are, (1) Do human resource, organization resource and strategy have significance influence towards restaurant performance in Malang? (2) Does human resource have dominant influence to performance? (3) Do age and size have a relationship with human resource, human resource performance and organization resource which is different due to age category as well as size (employee quantity) to restaurant in Malang city? Thus, the aims this research are divided into 4, there are (1) testing and analyzing the influence of human resource, organization resource and strategy to the restaurant performance in Malang, (2) testing and analyzing how much organization resource and strategic has influence towards restaurants in Malang? (3) testing and analyzing the relationship between age and the size of restaurants with human resource, organization resource and restaurant performance in Malang, (4) testing and analyzing the difference of organization performance based on age and the size of restaurants in Malang. The sample of the Research is restaurants in Malang. Survey result is gained from interview and questionnaire on 35 restaurants in Malang. The data analysis that was used in order to answer the research problem is multiple regression and MANOVA. The results of the research are, first, human resource, organization resource and strategy have influence toward restaurant performance in Malang. Second, human resource is the most dominant variable that have influence on performance. Third, the category of age and size has a relationship between human resource, organization resource and restaurant performance in Malang. Lastly, performance, human resource and organization resource have different result based on age as well as size in the restaurants at Malang.